Ambivalent Concepts of the Border: Political Borders - Bodily Boundaries - Veronika Magyar-Haas (Social Work and Society)
The article analyzes the various interpretations of the concept of the border or boundary, and demonstrates their inherent ambivalences. That the drawing and dissolution of borders and boundaries are processes of demonstration as well as exercise of power, and are both products and producers of conflict, is elucidated both in literature and in the boundary discourses occurring in geography, politics, history and the social sciences. Subsequent to the interdisciplinary interpretations of the 'political border', it is shown how the topic of the border and boundary (Grenze) has been handled so far in German-language discussion in educational science and popular pedagogy. The boundaries of the body have been almost entirely neglected in these discussions. This area receives more extensive discussion here, both to further investigate the relevance of a boundary-theory perspective on the body for educational research, and also to expand the concept of the boundary to include additional aspects. The article makes the case for the recognition and acknowledgement of the body in its boundaried form, its state of exposure and its constitutive vulnerability - an understanding that, following Butler, creates political, ethical and social obligations and responsibilities with regard to the body and the conditions that surround it.